Colored UV adhesive and preparation method thereof

By using functional components and composite additive components in color UV glue, modifying nanocellulose and grafting antioxidant substances, and introducing styrene butadiene rubber segments, the oxidation problems and insufficient flexibility of color UV glue are solved, significantly improving its mechanical properties, adhesive properties and oxidation resistance, and extending its service life.

CN119592281AActive Publication Date: 2025-03-11AOLUN NEW MATERIAL TECH (JINAN) CO LTD

Patent Information

Application Number
CN202411843923.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-09-22
Filing Date
2024-12-14
Publication Date
2025-03-11
Estimated Expiration
2044-12-14

AI Technical Summary

Technical Problem

Colored UV glue is easily affected by oxidation during long-term use, resulting in decreased adhesive force or failure, falling off, fading color, poor flexibility, easy to crack, affecting service life and aesthetics.

Method used

Using functional components and composite additive components, the antioxidant and flexibility of colored UV glue is enhanced through the modification of nanocellulose and the grafting of 5-hydroxymethylfurfural, and the styrene butadiene rubber segment is introduced through the esterification reaction to improve the adhesive performance.

Benefits of technology

It significantly improves the tensile strength, 180° peel strength and adhesive properties of color UV glue, enhances the anti-oxidation performance and flexibility, extends the service life, and meets the industry's application needs for color UV glue.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592281A_ABST
    Figure CN119592281A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of UV adhesives, and discloses a colored UV adhesive and a preparation method thereof.The colored UV adhesive is prepared from epoxy modified acrylate, polyurethane modified acrylate, acrylic resin, a photoinitiator, a diluent, a defoaming agent, nano color paste, a functional component and a composite additive component. The prepared colored UV adhesive has excellent mechanical properties and oxidation resistance, the colored UV adhesive is prevented from being affected by oxidation in the use process, and the service life of the colored UV adhesive is further prolonged; by adding the composite additive component, the prepared color UV adhesive has excellent flexibility and adhesive property, can be crosslinked with a color UV adhesive base material, is not easy to damage and fall off under the action of external force, can form firm and stable connection with an adhered base material, and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of UV glue, and in particular to a colored UV glue and a preparation method thereof. Background Art

[0002] As a new type of material, UV glue has become an important role in intelligent manufacturing with its unique advantages. With the growth of market demand, the application of UV glue is also expanding; UV glue is also called ultraviolet light curing glue or photosensitive glue, which is mainly composed of photosensitive resin, photoinitiator and other additives. It is an adhesive material that can be quickly cured under ultraviolet light. Through chemical reaction, it can form a strong bonding layer in a short time to achieve bonding between various materials. UV glue has the advantages of environmental friendliness and fast curing speed. Colored UV glue combines ultraviolet curing technology and color characteristics. It is composed of photosensitive resin, pigment, photoinitiator and other additives. Colored UV glue can further meet the diversified needs of the market. Colored UV glue is currently widely used in handicrafts and decorations, electronic and electrical industries, medical supplies, optics, architectural decoration, automobile manufacturing and other fields. Colored UV glue can also be used for the bonding of opaque materials, such as ceramics, metals, stones, plastics and other materials. Therefore, with the continuous development and growth of the application market of colored UV glue, the research on colored UV glue is of great significance.

[0003] During long-term use, colored UV glue is easily affected by oxidation, resulting in delamination between the UV glue and the adhered substrate, reduced or failed bonding force, resulting in shedding, and fading of color, affecting the aesthetics, overall performance and service life. In addition, the current colored UV glue has poor flexibility and cannot effectively disperse stress at the bonding interface. Stress concentration causes damage to the bonding part, which is prone to cracking and affects the bonding effect. Poor flexibility makes it more prone to aging. Therefore, the antioxidant performance, flexibility, bonding performance and mechanical properties of the colored UV glue should be modified to extend the service life of the colored UV glue and meet the industry's application needs for the colored UV glue. Therefore, the present invention provides a colored UV glue with broad application prospects. Summary of the invention

[0004] In order to solve the problems mentioned in the background technology, the object of the present invention is to provide a colored UV glue and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions: A colored UV adhesive comprises the following raw materials in parts by weight: 20-35 parts of epoxy modified acrylate, 20-35 parts of polyurethane modified acrylate, 20-30 parts of acrylic resin, 1-4 parts of photoinitiator, 5-10 parts of diluent, 0.5-2 parts of defoamer, 1-4 parts of nano color paste, 2-5 parts of functional components and 3-6 parts of composite additive components.

[0006] Furthermore, the photoinitiator is any one of 1-hydroxycyclohexyl phenyl ketone, benzophenone or 2-hydroxy-2-methyl-1-phenylpropanone; the diluent is isopropanol; and the defoaming agent is polydimethylsiloxane.

[0007] Furthermore, the preparation of the functional component comprises the following steps: S1. Ultrasonic dispersion of nanocellulose in toluene to form a uniform dispersion, adding ethyl 2-chloroisocyanate and a catalyst under a nitrogen atmosphere, raising the temperature to 50-60°C and stirring the reaction for 3-5h. After the reaction is completed, suction filtration, washing, and drying are performed to obtain modified nanocellulose; S2. Add the modified nanocellulose into dimethyl sulfoxide and disperse it evenly. Then, add 5-hydroxymethylfurfural and an alkaline catalyst under a nitrogen atmosphere, raise the temperature to 60-75°C, and react for 4-6 hours. After the reaction is completed, filter, wash, and dry to obtain functional components.

[0008] By adopting the above technical scheme, the surface of nanocellulose contains active hydroxyl groups, which can react with the isocyanate groups in the structure of 2-ethyl chloroisocyanate under the action of a catalyst to undergo an amination reaction, thereby introducing chlorine substituents on the surface of nanocellulose to obtain modified nanocellulose. Under the action of an alkaline catalyst, the chlorine substituents in the modified nanocellulose can undergo a substitution reaction with the active hydroxyl groups in the structure of 5-hydroxymethylfurfural to obtain a functional component. The functional component uses nanocellulose as a matrix material, and the nanocellulose has high mechanical strength and can be evenly dispersed in the matrix material of the color UV glue, thereby enhancing the binding force between nanocellulose and the matrix material of the color UV glue, thereby improving the mechanical properties of the color UV glue. In addition, 5-hydroxymethylfurfural is grafted into the modified nanocellulose in a chemically bonded manner, so that the functional component has excellent antioxidant properties, and at the same time effectively improves the problem that the small molecule antioxidant 5-hydroxymethylfurfural is easy to migrate and precipitate, ensuring that the antioxidant can act on the matrix material of the color UV glue for a long time, making the color UV glue not easy to oxidize, resulting in adhesion decline or failure and causing the color UV glue to fall off, thereby extending the service life of the color UV glue.

[0009] Furthermore, in S1, the catalyst is dibutyltin dilaurate or stannous octoate.

[0010] Furthermore, in S2, the alkaline catalyst is potassium carbonate or potassium bicarbonate.

[0011] Further, the preparation of the composite additive component is as follows: The hydroxy-terminated liquid styrene-butadiene rubber is stirred and dispersed in acetone, and then carboxymethyl guar gum and a composite catalyst are added, and the reaction is stirred at room temperature for 4-6 hours. After the reaction is completed, the solvent is removed, the product is collected, washed, and vacuum-dried to obtain a composite additive component.

[0012] By adopting the above technical scheme, the terminal hydroxyl group in the structure of the hydroxyl-terminated liquid styrene-butadiene rubber can undergo an esterification reaction with the carboxyl group in the structure of the carboxymethyl guar gum under the action of a composite catalyst to obtain a composite additive component. The unsaturated olefinic group contained in the structure of the composite additive component can participate in the preparation process of the color UV glue matrix material, and the composite additive component can be cross-linked with the color UV glue matrix material, thereby introducing a styrene-butadiene rubber segment with good flexibility into the color UV glue, which can undergo various forms of deformation when subjected to external force, thereby enhancing the flexibility of the color UV glue and making it less likely to be damaged and fall off. At the same time, the functional component structure contains a large number of hydroxyl groups and ester groups generated by the reaction, which increases the hydrogen bonding sites, thereby enhancing the interaction force between the color UV glue and the bonded substrate, making the contact closer, and forming a firm and stable connection at the interface between the color UV glue and the bonded substrate, thereby improving the bonding performance of the color UV glue.

[0013] Furthermore, the average relative molecular mass of the hydroxyl-terminated liquid styrene-butadiene rubber is 3000.

[0014] Furthermore, the composite catalyst is dicyclohexylcarbodiimide and 4-dimethylaminopyridine in a mass ratio of 2-6:1-1.5.

[0015] A method for preparing colored UV glue comprises the following steps: Step 1: adding epoxy modified acrylate, polyurethane modified acrylate and acrylic resin into a stirring kettle, raising the temperature to 60-90° C., adding diluent, defoamer, nano color paste, functional component and composite additive component, stirring for 1-3 hours to obtain a mixture; Step 2: Add a photoinitiator to the mixture, stir at a speed of 100-200 r / min for 20-50 min, let stand for 1-2 h, cool and discharge the mixture to obtain a colored UV adhesive.

[0016] Furthermore, in step 1, the stirring speed is 500-650r / min.

[0017] Beneficial effects of the present invention: The present invention adds functional components and composite additive components into the base material of the colored UV glue, so that the prepared colored UV glue has a tensile strength of up to 21.4 MPa and a 180° peel strength of up to 23.4 N / 25 mm, and has excellent bonding performance, and can form a firm and stable connection with the bonded substrate. At the same time, the present invention has excellent antioxidant performance and flexibility, and can prevent the colored UV glue from being affected by oxidation, resulting in a decrease in bonding or failure and resulting in shedding. The colored UV glue is not easily damaged or shedding when subjected to external force, and has a long service life and broad application prospects.

[0018] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0020] Figure 1 is the infrared spectrum of the functional components in the present invention; Figure 2 This is the infrared spectrum of the composite added components of the present invention. DETAILED DESCRIPTION

[0021] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] The preparation of the functional components in the following examples and comparative examples of the present invention is as follows: S1. 3 g of nanocellulose was ultrasonically dispersed in toluene to form a uniform dispersion. Under a nitrogen atmosphere, 2.6 g of ethyl 2-chloroisocyanate and 0.1 g of dibutyltin dilaurate were added. The temperature was raised to 55 ° C and stirred for 4 h. After the reaction was completed, the modified nanocellulose was filtered, washed, and dried to obtain; S2. Add 2.8 g of modified nanocellulose to dimethyl sulfoxide and disperse evenly. Then, under a nitrogen atmosphere, add 2.2 g of 5-hydroxymethylfurfural and 0.2 g of potassium bicarbonate. Raise the temperature to 70°C and react for 5 hours. After the reaction is completed, filter, wash and dry to obtain functional components.

[0023] The sample was prepared by potassium bromide tablet method, and the functional components were tested by Fourier infrared spectrometer, such as Figure 1 As shown, the spectral wavenumber test range is 4000cm -1 -500cm -1 , analysis shows that in the infrared spectrum of the functional components, 3318cm -1 The absorption peak of NH appeared at 2926-2856cm -1 The absorption peaks of CH in methyl and methylene appeared at 2720 cm -1 The absorption peak of CH in the aldehyde group appeared at 1710 cm -1 The absorption peak of C=O in carbamate appeared at 1672 cm -1 The absorption peak of C=O in the aldehyde group appeared at 1540 cm -1 The absorption peak of CN appeared at 1410 cm -1 The absorption peak of furan ring appeared at 1134 cm -1 The absorption peak of ether bond appeared at

[0024] The preparation of the composite additive components in the following examples and comparative examples of the present invention is as follows: 3.2 g of hydroxy-terminated liquid styrene-butadiene rubber with an average relative molecular mass of 3000 was stirred and dispersed in acetone, and then 2.6 g of carboxymethyl guar gum, 0.3 g of dicyclohexylcarbodiimide and 0.1 g of 4-dimethylaminopyridine were added. The mixture was stirred and reacted at room temperature for 6 h. After the reaction was completed, the solvent was removed, the product was collected, washed, and vacuum dried to obtain a composite additive component.

[0025] The sample was prepared by potassium bromide tablet method, and the composite added components were tested by infrared spectrometer, such as Figure 2 As shown, the spectral wavenumber test range is 4000cm -1 -500cm -1 , analysis shows that in the infrared spectrum of the composite additive component, 3056cm -1 The absorption peak of the carbon-hydrogen bond in the carbon-carbon double bond appears at 3024 cm -1 The absorption peak of the carbon-hydrogen bond in the benzene ring appeared at 1730 cm -1 The absorption peak of ester group appeared at 1657cm -1 The absorption peak of galactose / mannose ring appeared at 1601cm -1 、1492cm -1 The absorption peak of the benzene ring skeleton appeared at 1022cm -1 The absorption peak of COC in the pyran ring appeared.

[0026] Example 1, preparation of colored UV glue; Step 1: add 20g of epoxy modified acrylate, 20g of polyurethane modified acrylate and 20g of acrylic resin into a stirring kettle, raise the temperature to 60°C, add 5g of isopropyl ketone, 0.5g of polydimethylsiloxane, 1g of nano color paste, 2g of functional component and 3g of composite additive component, stir at a speed of 500r / min for 1h to obtain a mixture; Step 2: Add 1 g of 1-hydroxycyclohexyl phenyl ketone photoinitiator to the mixture, stir at a speed of 100 r / min for 20 min, let stand for 1 h, cool and discharge the material to obtain a colored UV adhesive.

[0027] Example 2, preparation of colored UV glue; Step 1, add 25g of epoxy modified acrylate, 25g of polyurethane modified acrylate, and 25g of acrylic resin into a stirring kettle, raise the temperature to 70°C, add 6g of isopropyl ketone, 1g of polydimethylsiloxane, 2g of nano color paste, 3g of functional component, and 4g of composite additive component, stir at a speed of 550r / min for 2h to obtain a mixture; Step 2: Add 2 g of 1-hydroxycyclohexyl phenyl ketone photoinitiator to the mixture, stir at a speed of 150 r / min for 30 min, let stand for 1.5 h, cool and discharge the material to obtain a colored UV adhesive.

[0028] Example 3, preparation of colored UV glue; Step 1: add 30g of epoxy modified acrylate, 30g of polyurethane modified acrylate and 30g of acrylic resin into a stirring kettle, raise the temperature to 80°C, add 8g of isopropyl ketone, 1.5g of polydimethylsiloxane, 3g of nano color paste, 4g of functional component and 5g of composite additive component, stir at a speed of 600r / min for 2.5h to obtain a mixture; Step 2: Add 3 g of 1-hydroxycyclohexyl phenyl ketone photoinitiator to the mixture, stir at a speed of 175 r / min for 40 min, let stand for 2 h, cool and discharge the material to obtain a colored UV adhesive.

[0029] Example 4, preparation of colored UV glue; Step 1: add 35g of epoxy modified acrylate, 35g of polyurethane modified acrylate and 30g of acrylic resin into a stirring kettle, raise the temperature to 90°C, add 10g of isopropyl ketone, 2g of polydimethylsiloxane, 4g of nano color paste, 5g of functional component and 6g of composite additive component, stir at a speed of 650r / min for 3h to obtain a mixture; Step 2: Add 4 g of 1-hydroxycyclohexyl phenyl ketone photoinitiator to the mixture, stir at a speed of 200 r / min for 50 min, let stand for 2 h, cool and discharge the material to obtain a colored UV adhesive.

[0030] Comparative Example 1, preparation of colored UV adhesive; Step 1, add 25g of epoxy modified acrylate, 25g of polyurethane modified acrylate, and 25g of acrylic resin into a stirring kettle, raise the temperature to 70°C, add 6g of isopropyl ketone, 1g of polydimethylsiloxane, 2g of nano color paste, and 4g of composite additive components, and stir at a speed of 550r / min for 2h to obtain a mixture; Step 2: Add 2 g of 1-hydroxycyclohexyl phenyl ketone photoinitiator to the mixture, stir at a speed of 150 r / min for 30 min, let stand for 1.5 h, cool and discharge the material to obtain a colored UV adhesive.

[0031] Comparative Example 2, preparation of colored UV adhesive; Step 1, add 25g of epoxy modified acrylate, 25g of polyurethane modified acrylate, and 25g of acrylic resin into a stirring kettle, raise the temperature to 70°C, add 6g of isopropyl ketone, 1g of polydimethylsiloxane, 2g of nano color paste, and 3g of functional components, and stir at a speed of 550r / min for 2h to obtain a mixture; Step 2: Add 2 g of 1-hydroxycyclohexyl phenyl ketone photoinitiator to the mixture, stir at a speed of 150 r / min for 30 min, let stand for 1.5 h, cool and discharge the material to obtain a colored UV adhesive.

[0032] Comparative Example 3, preparation of colored UV adhesive; Step 1, add 25g of epoxy modified acrylate, 25g of polyurethane modified acrylate, and 25g of acrylic resin into a stirring kettle, raise the temperature to 70°C, add 6g of isopropyl ketone, 1g of polydimethylsiloxane, 2g of nano color paste, 3g of nano cellulose, and 4g of composite additive components, stir at a speed of 550r / min for 2h to obtain a mixture; Step 2: Add 2 g of 1-hydroxycyclohexyl phenyl ketone photoinitiator to the mixture, stir at a speed of 150 r / min for 30 min, let stand for 1.5 h, cool and discharge the material to obtain a colored UV adhesive.

[0033] Comparative Example 4, preparation of colored UV adhesive; Step 1: add 25g of epoxy-modified acrylate, 25g of polyurethane-modified acrylate and 25g of acrylic resin into a stirring kettle, raise the temperature to 70°C, add 6g of isopropyl ketone, 1g of polydimethylsiloxane, 2g of nano-color paste, 3g of functional component and 4g of hydroxy-terminated liquid styrene-butadiene rubber, and stir at a speed of 550r / min for 2h to obtain a mixture; Step 2: Add 2 g of 1-hydroxycyclohexyl phenyl ketone photoinitiator to the mixture, stir at a speed of 150 r / min for 30 min, let stand for 1.5 h, cool and discharge the material to obtain a colored UV adhesive.

[0034] Performance Testing The colored UV glue prepared in Examples 1 to 4 and Comparative Examples 1 to 4 was heated to 100 mW / cm 2 The samples were irradiated with a 365nm ultraviolet lamp for 30s and then prepared into samples that met the test specifications. According to the GB / T 30776-2014 standard, the tensile strength of the samples was tested to determine the mechanical properties of the colored UV glue. According to the GB / T 2792-2014 standard, the samples were subjected to a 180° peel strength test to determine the bonding performance of the colored UV glue. After the samples were placed in an 80° aging box for 72h, the 180° peel strength test was performed again to determine the antioxidant properties of the colored UV glue. According to the GB / T 1731-2020 standard, the flexibility of the samples was tested to determine the flexibility of the colored UV glue. The test results are shown in the following table:

[0035] As can be seen from the above table, the colored UV glue prepared by Examples 1 to 4 of the present invention has excellent mechanical properties, bonding properties, antioxidant properties and flexibility, among which Example 2 has the best test effect. Comparative Example 1 does not add functional components, and nanocellulose cannot be used to graft antioxidant 5-hydroxyfurfural to enhance the mechanical properties and antioxidant properties of the colored UV glue, so the mechanical properties test and antioxidant performance test results are poor; Comparative Example 2 does not add composite additives, and composite additives cannot be used to participate in the preparation process of the colored UV glue, introduce flexible styrene-butadiene rubber segments and increase hydrogen bonding sites to improve the flexibility and bonding properties of the colored UV glue, so the flexibility test and bonding performance test results are poor; Comparative Example 3 adds nanocellulose and composite additives, and since nanocellulose is not grafted with antioxidants, the antioxidant test results are poor; Comparative Example 4 adds functional components and hydroxyl-terminated liquid styrene-butadiene rubber, which can participate in the preparation process of the colored UV glue and enhance flexibility, but there are few hydrogen bonding sites, so the bonding performance test results of the colored UV glue are poor.

[0036] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A colored UV adhesive, characterized in that: The invention comprises the following raw materials in parts by weight: 20-35 parts of epoxy modified acrylate, 20-35 parts of polyurethane modified acrylate, 20-30 parts of acrylic resin, 1-4 parts of photoinitiator, 5-10 parts of diluent, 0.5-2 parts of defoamer, 1-4 parts of nano color paste, 2-5 parts of functional components and 3-6 parts of composite additive components.

2. A colored UV adhesive according to claim 1, characterized in that: The photoinitiator is any one of 1-hydroxycyclohexyl phenyl ketone, benzophenone or 2-hydroxy-2-methyl-1-phenylpropanone; the diluent is isopropanol; and the defoaming agent is polydimethylsiloxane.

3. The color UV glue according to claim 1, characterized in that: The preparation of the functional component comprises the following steps: S1. Ultrasonic dispersion of nanocellulose in toluene to form a uniform dispersion, adding ethyl 2-chloroisocyanate and a catalyst under a nitrogen atmosphere, raising the temperature to 50-60°C and stirring the reaction for 3-5h. After the reaction is completed, suction filtration, washing, and drying are performed to obtain modified nanocellulose; S2. Add the modified nanocellulose into dimethyl sulfoxide and disperse it evenly. Then, add 5-hydroxymethylfurfural and an alkaline catalyst under a nitrogen atmosphere, raise the temperature to 60-75°C, and react for 4-6 hours. After the reaction is completed, filter, wash, and dry to obtain functional components.

4. The color UV adhesive according to claim 3, characterized in that: In S1, the catalyst is dibutyltin dilaurate or stannous octoate.

5. The color UV adhesive according to claim 3, characterized in that: In S2, the alkaline catalyst is potassium carbonate or potassium bicarbonate.

6. The color UV adhesive according to claim 1, characterized in that: The preparation of the composite additive component is as follows: The hydroxy-terminated liquid styrene-butadiene rubber is stirred and dispersed in acetone, and then carboxymethyl guar gum and a composite catalyst are added, and the reaction is stirred at room temperature for 4-6 hours. After the reaction is completed, the solvent is removed, the product is collected, washed, and vacuum-dried to obtain a composite additive component.

7. The color UV adhesive according to claim 6, characterized in that: The average relative molecular mass of the hydroxyl-terminated liquid styrene-butadiene rubber is 3000.

8. The colored UV adhesive according to claim 6, characterized in that: The composite catalyst is dicyclohexylcarbodiimide and 4-dimethylaminopyridine in a mass ratio of 2-6:1-1.

5.

9. A method for preparing colored UV glue as claimed in claim 1, characterized in that: The following steps are involved: Step 1: adding epoxy modified acrylate, polyurethane modified acrylate and acrylic resin into a stirring kettle, raising the temperature to 60-90° C., adding diluent, defoamer, nano color paste, functional component and composite additive component, stirring for 1-3 hours to obtain a mixture; Step 2: Add a photoinitiator to the mixture, stir at a speed of 100-200 r / min for 20-50 min, let stand for 1-2 h, cool and discharge the mixture to obtain a colored UV adhesive.

10. The method for preparing a colored UV adhesive according to claim 9, characterized in that: In step 1, the stirring speed is 500-650r / min.

Citation Information

Patent Citations

  • Colored UV adhesive and preparation method thereof

    CN109913155A

  • UV adhesive and preparation method thereof

    CN116200166A

  • UV (ultraviolet) adhesive as well as preparation method and application thereof

    CN116656297A

  • Block-structure UV adhesive for sensing coil, and preparation method therefor

    WO2024138658A1

Cited By

  • Low-temperature adhesive for double-layer composite adhesive sticker and preparation method of low-temperature adhesive

    CN119979115A